Promoting the uptake of preventative Aboriginal child health policy in Western Australia. (December 2015) - Bradshaw, Sue; Hellwig, Leonie; Peate, Diann; Wilson, Anne
Abstract: Problem: Australian Aboriginal children are over‐represented on all negative health indicators compared with non‐Aboriginal children.Contributing factors to the disparity include the impact of historical events, racism and social determinants of health. Despite the benefits of child health checks, offered through the Medicare Benefit Schedule and community health services, uptake of these is low. Design: In 2012, Western Australia Health implemented the Enhanced Aboriginal Child Health Schedule (EACHS) policy to address specific health needs of Aboriginal children. The Aboriginal Child Heath Project (the Project), was a five‐year initiative funded through the Council of Australian Governments. Project staff promoted the profile of preventative child health and the uptake of the EACHS policy across the state by agencies operating in the sector. Setting: Western Australia. Key measurements for improvement: Reach of the implementation workshop was measured by the number of staff attending policy implementation and the total number for agencies represented. One measure of impact was the number of agencies requesting the EACHS policy who adapted or adopted it to deliver evidence based comprehensive child health programs. Strategies for change: The Project offered policy implementation workshops to health staff delivering services to young Aboriginal children. In addition to the evidence‐based policy, a suite of resources were made available to support service delivery. Effects of change: The EACHS is a framework used by agencies to deliver consistent care and support governance when providing child health services to Aboriginal families across Western Australia. Lessons learnt: Providing a policy that was consistent with identified service strengths allowed agencies to individually build their capacity to deliver child health checks, using existing resources, at their own pace.